The Influence of Conformity and Family Economic Education on Consumption Behavior of High School Students in Mojokerto City - Ikrima Renanda Afina Dyahfirdania; Eka Nurlaili (International Journal of Emerging Research and Review, 2023)
Objective: High school students who are in their teens tend to consume or buy because they always follow trends without seeing the motives for their needs, and without paying attention to whether the items purchased are really needed or not. This study aims to analyze the influence of conformity and family economic education on the consumption behavior of High School Students in Mojokerto City. Method: The analysis technique used was multiple linear regression analysis using IBM SPSS 22 software. The number of samples in this study were 323 students.  Results: In this study, there are results that there is a partial influence of conformity on consumption behavior, there is a partial influence of family economic education on consumption behavior. Also, there is a simultaneous influence of conformity and family economic education on consumption behavior. The results of this study indicate that all independent variables in this model can be said to be appropriate and significant and have a contribution to the dependent variable. Novelty: This research can provide an overview of the influence of economic education in the family environment and conformity to the consumption behavior of high school students in Mojokerto City.